THE IMPORTANCE OF EXECUTIVE FUNCTIONS FOR LEARNING - de Carvalho, Aline dos Santos Moreira; Altoé, Jacqueline David; Silva, Diego de Almeida; e Silva, Ivaneide da Silva; e Silva, Vanessa de Almeida; Jagobucci, Lucélia; Baptista, Barbara Caze; da Silva, Eliete Regina Alves; Corrêa, Thais Ribeiro; da Silva, Zelia; Barros, Renata Cristina da Conceição; Tenorio, Marcella; et al. (Seven Editora, 2025)
This article aims to review the literature on the importance of executive functions (EFs) in the learning process. Executive functions are essential cognitive skills that include inhibitory control, working memory, and cognitive flexibility, which are fundamental for academic success and child development. The justification for the study is based on the growing relevance of understanding how these functions can impact academic performance, especially in an educational context that demands increasingly complex and integrated skills. The methodology used was a literature review, with analysis of studies already published on the relationship between executive functions and learning in children and adolescents. Articles from scientific journals and specialized books that discuss the development and evaluation of executive functions, as well as educational interventions, were selected. The result of the review pointed out that children with more developed executive skills tend to perform better in subjects such as mathematics and reading, in addition to demonstrating a greater ability to solve complex problems. The review also highlighted the effectiveness of intervention programs that stimulate these skills, suggesting that executive function training can be a powerful tool to improve school performance and reduce behavior problems. It is concluded that executive functions play a crucial role in learning and should be incorporated into pedagogical strategies.DOI: https://doi.org/10.56238/sevened2025.018-025